Properties and one-step synthesis of (2-acetylpyridine)tetraammineruthenium(II), [Ru-II(2-acpy)(NH3)(4)](2+) and tetraammine(2-benzoylpyridine)ruthenium(II), [Ru-II(NH3)(4)(2-bzpy)](2+) Redox potentials, UV-Vis and NMR spectra - de Paula, ASAT; Mann, B. E.; Tfouni, E. (Elsevier B.V., 1999)
A more direct and efficient route to the syntheses of [Ru(NH3)(4)(X-Y)](BF4)(2), where X-Y can be 2-acetylpyridine (2-acpy) or 2-benzoylpyridine (2-bzpy), based on the reactions of [RuCl(NH3)(5)]Cl-2 with these ortho-substituted azines is described. The [Ru(2-acpy)(NH3)(4)](BF4)(2) and [Ru(NH3)(5)(2-bzpy)](BF4)(2) complexes have a molar conductance of 328 and 292 Ohm(-1) cm(2) mol(-1), respectively, corresponding to a 1:2 species in solution. These complexes showed two intense absorption bands around 620-650 and 380 nm, the energies of which are solvent dependent, decreasing with the increase of the Gutman's donor number of the solvent, and were assigned as metal-to-ligand charge transfer (MLCT). The complexes have oxidation potentials (Ru-II/III) of +0.380 V vs. Ag/AgCl (2-acpy) and +0.400 V vs. Ag/AgCl (2-bzpy), and reduction potentials (X-Y0/-) of -1.10 V vs. Ag/AgCl (2-acpy) and -0.950 V vs. Ag/AgCl (2-bzpy) on CF3COOH/NaCF3COO at pH=3.0, scan rate 100 mV s(-1), [Ru]=1.0x10(-3) mol l(-1). Both processes show a coupled chemical reaction. Upon oxidation of the metal center, the MLCT absorption bands are bleached and restored upon subsequent reduction. In order to confirm the structure of the complexes a detailed LH NMR investigation was performed in d(6)-acetone. Further confirmation of the structure was obtained by recording the N-15 NMR spectrum of [Ru(NH3)(4)(2-bzpy)](2+) in d(6)-DMSO using the INEPT pulse sequence improving the sensitivity of N-15 by polarization transfer from the protons to the N-15. The Nuclear Overhauser Effect (NOE) experiments were made qualitatively for [Ru(NH3)(4)(2-acpy)](2+), and showed that H-6 of the pyridine is close to a NH3 proton, which should then be in a cis position, and, hence, confirming that acpy is acting as a bidentate ligand. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: rutheniumtetraammine; inert ammonias; N-15 NMR